Niepewna normalizacja stosunków polityczno-gospodarczych Iranu z zachodem - Gwiazda, Adam (Wydawnictwo Naukowe Wydziału Nauk Politycznych i Dziennikarstwa Uniwersytetu im. Adama Mickiewicza w Poznaniu, 2015)
Celem artykułu jest analiza dotychczasowych osiągnięć negocjacji prowadzonych przez pię¬ciu stałych członków Rady Bezpieczeństwa ONZ i Niemiec z władzami Iranu. Negocjacje skierowane są na ograniczenie irańskiego programu nuklearnego i normalizację wzajemnych stosunków. Porozumienie tymczasowe, podpisane w listopadzie 2013 r. w Genewie nie doprowadziło do zawarcia ostatecznych uzgodnień. Wynegocjowane 2 kwietnia 2015 r. porozumienie ramowe z Lozanny, choć powinno być uznane za sukces przez fakt prowadzenia rozmów, to brak konkretnych ustaleń nakazuje uznać je za negocjacyjne niepowodzenie.

This article analyses and assesses the hitherto achievements in the negotiations of the five permanent members of the Security Council plus Germany with Iran devoted to the limitation of its nuclear program and normalization of the mutual relations. This is prerequisite of the full nor-malization of political and economic relations between Iran and Western states. An interim agreement struck in the end of November 2013 in Geneva has not led, for the time being, to the signing of the permanent agreement. On the contrary, the negotiations were extended for the third time since November 2013 till June 2015. There is a danger that Iran will get another exten¬sion in June this year and will be able to play for time again. Thus it is reasonable to doubt whether Iran wants a deal with the West or tries to produce a nuclear bomb in the near future, The Obama administration conducts rather „soft” policy towards Iran as the U.S. needs that country in the war with the Islamic State. On the other hand even the present U.S. administration cannot accept a deal that allows Iran to expand its nuclear programme and enrich uranium to 20%. From various reasons the present stalemate in the negotiations with Iran cannot be resolved with the use of military force. Thus the only hope is that Iran will reconsider all benefits connected with the normalization of its economic and political relations with the West and finally sign a deal with the United States and other Western states.
Uncertain Normalization of Political and Economic Relations of Iran With the West